THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK COMPETENCE AND COMPENSATION TOWARDS THE PERFORMANCE OF THE HEAD OF MADRASAH TSANAWIYAH IN DELI SERDANG DISTRICT - Amiruddin, Amiruddin; Situmorang, Benyamin; Zainuddin, Zainuddin (Universitas Dharmawangsa Medan, 2020)
This study aims to address the problems of the eleven hypotheses proposed, which include 1) the direct influence of organizational culture on compensation, 2) the direct effect of work competence on compensation, 3) the direct influence of organizational culture on the performance of the madrasa head, 4) the direct effect of work competence on performance madrasah head, 5) direct effect of compensation on madrasa head performance. The population of this study was the Head of Madrasas as many as 133 people with a total sample of 103 people taken using the Krejcie and Morgan tables. The research instrument was a questionnaire with a Likert scale and tests. The research data is processed and analyzed by path analysis path analysis. This path analysis begins by testing the analysis requirements including the normality test through the Lilifors formula, and the linearity and regression significance test. The results of the analysis show there is a direct influence of organizational culture on compensation with a path coefficient of 0.285, a direct effect of work competence on compensation with a path coefficient of 0.286, Likewise, there is a direct effect of organizational culture on the performance of madrasah heads with a path coefficient of 0.216, there is a direct influence of work competence on the performance of madrasa head with a path coefficient of 0.171, there is a direct effect of workers compensation on the performance of the madrasa head with a path coefficient of 0.178. This study aims to address the problems of the eleven hypotheses proposed, which include 1) the direct influence of organizational culture on compensation, 2) the direct effect of work competence on compensation, 3) the direct influence of organizational culture on the performance of the madrasa head, 4) the direct effect of work competence on the headmaster's performance, 5) the direct effect of compensation on the headmaster's performance. The population of this study was the Head of Madrasas as many as 133 people with a total sample of 103 people taken using the Krejcie and Morgan tables. The research instrument was a questionnaire with a Likert scale and tests. The research data is processed and analyzed by path analysis. This path analysis begins by testing the analysis requirements including the normality test through the Lilifors formula, and the linearity and significance test of regression. The results of the analysis show there is a direct influence of organizational culture on compensation with a path coefficient of 0.285, a direct effect of work competence on compensation with a path coefficient of 0.286, Likewise, there is a direct effect of organizational culture on the performance of madrasas head with a path coefficient of 0.216, there is a direct influence of work competence on the performance of madrasa head with a path coefficient of 0.171, there is a direct effect of workers compensation on the performance of the madrasa head with a path coefficient of 0.178.